Pengaruh Harga, Fasilitas Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Kopi Kenangan Di Kota Bekasi: (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Alfito Surya Saputra; M.Fadhli Nursal; Franciscus Dwikotjo Sri Sumantyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The influence of price, facilities and service quality on customer satisfaction with memorable coffee in the city of Bekasi (study of management study program students class of 2020, Bhayangkara University, Jakarta Raya). This research aims to determine partially and simultaneously the relationship between price, facilities and service quality on customer satisfaction with memorable coffee in the city of Bekasi. This research is research with a quantitative approach, a technique based on the philosophy of positivism that is used is the Slovin formula. The population in this study were all The Originate consumers in the 2020 Management study program, Bhayangkara University, Greater Jakarta with a sample of 155 respondents. Data processing and hypothesis testing using SmartPLS 4 software. The research results show that price has no partial effect on customer satisfaction. Facilities partially have a positive effect on customer satisfaction. Service quality partially has a positive effect on customer satisfaction. Simultaneous test results show that price, facilities and service quality simultaneously influence customer satisfaction